2014
DOI: 10.1093/ejcts/ezu393
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of imaging techniques for the assessment of tumour progression in an orthotopic rat model of malignant pleural mesothelioma†

Abstract: MRI is a reliable and reproducible noninvasive in vivo imaging method for MPM tumour burden assessment for the present MPM model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…By immunohistochemistry, the immunoreactivity of Merlin was also detected in both cytoplasmic and nuclear fractions of Met5A and was negative in Mero‐82 cells (Supplementary Figure 1C). Tumors derived from orthotopic implantation of rat MPM cells (IL45; Merlin positive) collected in our previous study (Meerang et al., 2015) were positively stained, mainly in the cytoplasm. Xenograft tumors, derived from a human MPM cell line negative for Merlin (ZL55), show very weak‐negative staining in both nuclear and cytoplasmic fractions (Supplementary Figure 1C).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…By immunohistochemistry, the immunoreactivity of Merlin was also detected in both cytoplasmic and nuclear fractions of Met5A and was negative in Mero‐82 cells (Supplementary Figure 1C). Tumors derived from orthotopic implantation of rat MPM cells (IL45; Merlin positive) collected in our previous study (Meerang et al., 2015) were positively stained, mainly in the cytoplasm. Xenograft tumors, derived from a human MPM cell line negative for Merlin (ZL55), show very weak‐negative staining in both nuclear and cytoplasmic fractions (Supplementary Figure 1C).…”
Section: Resultsmentioning
confidence: 84%
“…By immunohistochemistry, the immunoreactivity of Merlin was also detected in both cytoplasmic and nuclear fractions of Met5A and was negative in Mero-82 cells (Supplementary Figure 1C). Tumors derived from orthotopic implantation of rat MPM cells (IL45; Merlin positive) collected in our previous study (Meerang et al, 2015) were positively stained, mainly in the cytoplasm.…”
Section: Markers Expression and Their Association With Clinical And P...mentioning
confidence: 83%
“…Different analytical methods have been developed for in situ tumor visualization. Firefly luciferase (luc)-engineered cells can be detected by a non-invasive bioluminescence imaging method, as in rats injected with luc-MM cells in the pleural cavity (57). However, data have shown that magnetic resonance imaging (MRI) is a more reliable method for MPM tumor burden measurement compared to bioluminescence (57).…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…Firefly luciferase (luc)-engineered cells can be detected by a non-invasive bioluminescence imaging method, as in rats injected with luc-MM cells in the pleural cavity (57). However, data have shown that magnetic resonance imaging (MRI) is a more reliable method for MPM tumor burden measurement compared to bioluminescence (57). Computed tomography scanning may be also of interest, as shown with a lung cancer cell line in mice (58).…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…MR data sets were acquired applying T2-weighted fast spin-echo sequences in transverse/sagittal/ coronal orientation (repetition time TR 3,500 ms, echo time TE 45 ms). The tumor volume (mm 3 ) was quantified blindly with ImageJ software (NIH, Bethesda, MD) by two observers as we described previously (23).…”
Section: Tumor Imagingmentioning
confidence: 99%